Why do so many incompetent men become leaders? (and how to fix it) - Chamorro-Premuzic, Tomas (Boston Harvard Business Review Press, 2019)
In this provocative book, author Tomas Chamorro-Premuzic connects the dots and asks a powerful question: what if the reason for the lack of women at the top--and the presence of so many incompetent leaders who also happen to be men--is not that there are too many obstacles slowing women's advancement, but that there aren't enough career-testing obstacles for men? Marshalling decades of rigorous research on leadership to build his case, Chamorro-Premuzic points out that although women make up a minority of leaders, female leaders are often rated by both bosses and subordinates as more competent than their male peers. At the same time, most organizations continue to equate leadership potential with a handful of personality traits, like overconfidence and narcissism, that don't correlate with success. In other words, these traits may help people get nominated to leadership roles, but they backfire once the individual has the job
Keywords: Sex role in the work environment